Socialization of the Threats of Using Gadgets in Elementary School Students (SDN 48 Ternate City) - Dwi Widyastuti Nurharyanto; Iwan Abdy; Hutri Handayani Isra; Yulia Novita Sari (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
The development of increasingly sophisticated times and supported by the Revolution 5.0 era makes the use of gadgets increasingly important to support daily activities. Apart from providing convenience, gadgets also have a negative impact, especially on elementary school students. Elementary school students who are unable to control themselves when using gadgets become addicted to the features they contain, such as social media and games. This has an impact on low learning achievement and decreased study habits. To overcome this, the first step taken is to carry outreach, to provide direction to related parties in the school, in this case teachers and students. The outreach activity was held on June 13, 2023, at SD Negeri 48 Ternate City. This school was chosen because it is a partner school of the Khairun University Primary School Teacher Education Study Program (PGSD). The hope of this activity is that students can be wiser in using gadgets and cooperation from various parties is formed to be active in making this happen. This outreach activity is published in the form of scientific articles. The wider public can access this article to use as a reference and provide an understanding of the wise use of gadgets for elementary school students.